Problematics of Legal Kincrease in The Sale Value of Taxable Objects - Land and Building Tax (NJOP-PBB) on The Process of Transfer of Land Rights at The Office of The Land Deed Official in Blora Regency - Mar’ah, Nurul; Purnawan, Amin (TABELLIUS: Journal of Law, 2025)
Abstract. The purpose of this study is to determine and analyze the impact of the increase in the Taxable Object Sales Value - Land and Building Tax (NJOP - PBB) on the process of transferring land rights at the Notary's Office - Land Deed Making Official (PPAT), to determine the obstacles and efforts made related to the increase in the Taxable Object Sales Value - Land and Building Tax (NJOP - PBB) on the process of transferring land rights at the Notary's Office - Land Deed Making Official (PPAT). The approach method in this study is the sociological juridical approach, namely an approach that emphasizes research that aims to obtain legal knowledge empirically by going directly to the object. The data used are primary and secondary data obtained through interviews and literature studies, while the data analysis method is carried out by qualitative analysis. The results of the study concluded that the Increase in the Taxable Object Sales Value - Land and Building Tax (NJOP - PBB) certainly affects the process of transferring land rights, because it is not uncommon for the transaction value submitted by taxpayers to be considered inappropriate by tax officers, so it is not uncommon for tax officers in the verification / validation process, to request that the transaction value be changed and adjusted according to the tax officer's assessment. The tax value that must be paid is very high, the taxable object sales value (NJOP) also always increases every year so that with the increasing taxable object sales value (NJOP), the tax that must be paid is the estimated value determined by the Regional Revenue, Financial Management and Asset Agency (BPPKAD) Office exceeds the original sale and purchase value so that the applicants feel very reluctant, so the local government must take concrete steps and appropriate solutions related to future policies.Keywords: Problems; Njop-PBB; PPAT.